Analisis Penalaran Hukum Terhadap Pembatalan Keputusan Gubernur DKI Jakarta Nomor 1517 Tahun 2021 Berdasarkan Premis Mayor dan Premis Minor (Studi Putusan 11/G/2022/PTUN JKT) - Anisah, Aura; Nirwana, Rena Putri; Sheila, Eirene Eva Marta; Amelia, Shelomita Putri; Harwanti, Apriliana Dwi; Rosadi, Adisty Aulia; Gumay, Davina Kheisya Alliyah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This article examines the form of legal reasoning in the case of annulment of DKI Jakarta Governor Decree Number 1517 of 2021 concerning the determination of the 2022 Provincial Minimum Wage (UMP) which was decided through the Jakarta State Administrative Court (PTUN) Decision Number 11/G/2022/PTUN JKT. The research was conducted using a literature study method and a case study approach to the decision. The legal reasoning in this study is built through major premises in the form of legal provisions governing wages in the Job Creation Law and its derivative regulations, and minor premises in the form of legal facts related to the determination of the DKI Jakarta UMP in 2022 as well as legal considerations from the panel of judges of the Jakarta Administrative Court. Based on the results of the analysis, it is known that the policy of the Governor of DKI Jakarta in raising the UMP exceeds the applicable provisions and is contrary to the principle of legality in the Indonesian legal system. Therefore, the Jakarta Administrative Court's decision to cancel the decision is considered to be in accordance with the principles of state administrative law and the provisions of the applicable laws and regulations.